Islamic civilization: awakening parameters - Kayadibi, Saim (International Institute of Advanced Studies (IAIS) Malaysia and Pluto Press (London), 2012)
The Muslim world’s significant contribution to the development of world civilisation deserves further investigation. History’s leading Muslim empires all assumed momentous responsibilities in adapting Islamic civilisation to changing times. The author argues that researching and studying the input of their intelligentsias and elites would be a necessary requirement for any Islamic ‘renaissance’. Western civilisation, often presented as the only civilisation that has enabled the world to progress, ignores the contributions of all other civilisations. This article underlines the significance of Islamic civilisation by exploring the Muslims’ reawakening process and humanity’s need for a new world system, one that reflects Islamic civilisation’s understanding and practice of ontological freedom, security, and human rights.